Conceptualizing transport transitions: Energy Cultures as an organizing framework. Issue 4 (1st October 2014) - Stephenson, Janet; Hopkins, Debbie; Doering, Adam
Abstract : The dominance of fossil fuel‐powered transport systems presents a serious risk to human well‐being and the natural environment. Transitioning to a low‐carbon transport system requires changes to many dimensions of transport, including: technologies, and mobility practices and expectations. It also requires changes across multiple scales of activity. Conceptual models play an essential role in transitions within complex systems such as transport, as they can help identify key interactions and opportunities for change. A variety of theoretical models offer useful perspectives on transport transitions from different disciplinary positions. In this paper, we introduce the Energy Cultures framework, which was developed to support interdisciplinary understandings of energy behavior and energy‐related transitions. It offers an integrating framework for transport behavior and a group of concepts to assist with analysis. We explore the potential of the framework in the transportation context by using the findings from a series of in‐depth interviews with international transport experts. Applied to the interview material, the framework provides a structure which works at different scales to highlight key influences that lock‐in the prevailing transport culture, as well as key drivers that are producing new emerging transport cultures. The framework complements other models and approaches, and offers a gateway to deeper exploration of the elements of interest via these complementary theories and models. We conclude that the Energy Cultures framework has the qualities of a successful integrating model for conceptualizing energy transitions in transport. WIREs Energy Environ 2015, 4:354–364. doi: 10.1002/wene.149 This article is categorized under: Energy Efficiency > Systems and Infrastructure Energy Infrastructure > Economics and Policy Energy Infrastructure > Systems and Infrastructure Energy and Development > Climate and Environment Abstract :